Abnormal degree centrality values as a potential imaging biomarker for major depressive disorder: A resting-state functional magnetic resonance imaging study and support vector machine analysis - Lin, Hang; Xiang, Xi; Huang, Junli; Xiong, Shihong; Ren, Hongwei; Gao, Yujun (Frontiers in Psychiatry, 2022)
Objective: Previous studies have revealed abnormal degree centrality (DC) in brain structural and functional networks in patients with MDD. However, DC was used to distinguish between MDD patients and healthy controls (HCs) combined with a support vector machine (SVM). Here, the researchers elucidated the variations in DC values in brain regions of MDD patients and provided imaging bases for clinical diagnosis. Methods: One hundred and ninety-eight patients with MDD and two hundred and thirty-four HCs were scanned by resting-state functional magnetic resonance imaging (rs-fMRI). DC and SVM were applied to analyze imaging data. Results: Compared with HCs, MDD patients displayed elevated DC values in the vermis, left anterior cerebellar lobe, hippocampus, and caudate, and depreciated DC values in the left posterior cerebellar lobe, left Insula, and right caudate. As per the results of the SVM analysis, DC values in the left anterior cerebellar lobe and right caudate could distinguish MDD from HCs with accuracy, sensitivity, and specificity of 87.71% (353/432), 84.85% (168/198), and 79.06% (185/234) respectively. Our analysis did not reveal any significant correlation among the DC value and the disease duration or symptom severity in patients with MDD. Conclusion: Our study demonstrated abnormal DC patterns in patients with MDD. Aberrant DC values in the left anterior cerebellar lobe and right caudate could be presented as a potential imaging biomarker for MDD diagnosis.